Plasmonic metal–semiconductor heterostructures for hot-electron-driven photochemistry. (January 2020) - Huang, Jiawei; Guo, Wenxiao; Hu, Yue; Wei, Wei David
Abstract: Abstract : Plasmonic nanostructures possess broadly tunable optical properties with catalytically active surfaces. They offer new opportunities for achieving efficient solar-to-chemical energy conversion. Plasmonic metal–semiconductor heterostructures have attracted heightened interest due to their capability of generating energetic hot electrons that can be collected to facilitate chemical reactions. In this article, we present a detailed survey of recent examples of plasmonic metal–semiconductor heterostructures for hot-electron-driven photochemistry, including plasmonic metal–oxide, plasmonic metal–two-dimensional materials, and plasmonic metal–metal–organic frameworks. We conclude with a discussion on the remaining challenges in the field and an outlook regarding future opportunities for designing high-performance plasmonic metal–semiconductor heterostructures for photochemistry.